Analysis of Internal Auditor Characteristics on Quality Audit Considerations in Educational Institutions - Caesar Bagus Pradana; Helmy Wahyu Sukiswo (JIEMAN: Journal of Islamic Educational Management, 2025)
The quality of audit judgment is a key factor in supporting the effectiveness of Internal Quality Audits (IQA) and the governance of educational institutions. This study aims to analyze the influence of internal auditors’ characteristics on the quality of audit judgment in educational institutions. The study employs a qualitative approach using library research, specifically a review of scientific articles published between 2018 and 2023. The data were analyzed using content analysis to identify similarities, differences, and gaps in research findings regarding the characteristics of internal auditors and audit judgment. The results indicate that auditors’ experience and professional skepticism are the primary characteristics contributing to the quality of audit judgment. Experienced auditors with professional skepticism are able to evaluate evidence more critically, identify risks accurately, and produce objective and accountable audit recommendations.  However, the impact of these two characteristics may vary depending on contextual factors, such as task complexity, organizational pressure, and the quality of auditor training. This study concludes that strengthening internal auditors’ competencies, experience, and professional skepticism are key factors in improving the quality of audit judgment, thereby supporting accountability, transparency, and continuous quality improvement in educational institutions.